Assessing m-Health success in Bangladesh: An empirical investigation using IS success models. Issue 5 (12th September 2016) - Hossain, Mohammad Alamgir
Abstract : Purpose: Mobile health, i.e. m-Health possesses huge potential, especially to the developing countries and remote locations of developed countries. The success of such systems may create a healthier society through eradicating health incidents, which cannot otherwise be addressed with "brick and mortar" type of health systems. The purpose of this paper is to develop an m-Health success model from users' perspective and validate in a developing country context. Design/methodology/approach: Epistemologically, positivist approach has been adopted for the current research. An initial research model was developed from existing information system (IS) literature, which was then validated with survey data applying partial least square structural equation modelling (PLS-SEM). Findings: The results summarise that continuance intention (CI) of m-Health services is dependent on perceived value (PV) and user satisfaction (STF); PV positively influences STF. Moreover, platform quality, quality of medical advice, and interaction quality have positive and direct effect on PV and STF; finally, CI drives to better quality of health life. Practical implications: The findings of this study provide strategic implications to health managers and practitioners recognising the determinants of m-Health success and comprehending their relationships. It is underscored that, in order to secure the success of an m-Health system in a given society both human and technology-related components are vital and therefore should be taken care of. Originality/value: This is the first attempt that develops and validates an m-Health system success model, particularly from the context of a country with low-health profile. Moreover, the contextualisation of the related variables and extension of existing IS success models is theoretically original.